2017
DOI: 10.1038/s41598-017-14376-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Dietary Medium-Chain Fatty Acid Ratio Mitigates High-fat Diet-Induced Non-Alcoholic Steatohepatitis by Regulating Autophagy

Abstract: Previous studies have demonstrated that saturated fatty acids (SFAs) are more lipotoxic than unsaturated fatty acids (UFAs) in inhibiting hepatic autophagy and promoting non-alcoholic steatohepatitis (NASH). However, there have been few studies have investigated the effects of carbon chain length on SFA-induced autophagy impairment and lipotoxicity. To investigate whether SFAs with shorter carbon chain lengths have differential effects on hepatic autophagy and NASH development, we partially replaced lard with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 53 publications
(66 reference statements)
4
28
1
Order By: Relevance
“…Though the role of medium chain fatty acid (MCFA) and medium chain triglycerides (MCT) seems controversial as MCT has been shown to cause steatosis, 36 while other studies have shown they reduce steatosis and hepatic injury by upregulating fatty acid liver oxidation. 37,38 Although MCFAs are associated with decreasing the ratio of Firmicutes to Bacteroidetes leading to a reduction in steatosis, we did not observe such changes in the HFF mice. In contrast, the LFF diet had over 4 times less fat than both the NAFLD-inducing and the HFF diets and the fat present was mainly enriched in omega-3 PUFAs.…”
Section: Discussioncontrasting
confidence: 73%
“…Though the role of medium chain fatty acid (MCFA) and medium chain triglycerides (MCT) seems controversial as MCT has been shown to cause steatosis, 36 while other studies have shown they reduce steatosis and hepatic injury by upregulating fatty acid liver oxidation. 37,38 Although MCFAs are associated with decreasing the ratio of Firmicutes to Bacteroidetes leading to a reduction in steatosis, we did not observe such changes in the HFF mice. In contrast, the LFF diet had over 4 times less fat than both the NAFLD-inducing and the HFF diets and the fat present was mainly enriched in omega-3 PUFAs.…”
Section: Discussioncontrasting
confidence: 73%
“…Modeling dyslipidemia in cultures of sensory DRG neurons also induces significant neuronal damage, including oxidative stress, impaired mitochondrial trafficking, dysfunctional axonal mitochondria, bioenergetic reprogramming, and neuronal dysfunction as a result of increased levels of LCSFAs (14-17, 27, 59, 60). In parallel, several recent studies also indicate that normalization of MCSFA levels in lard-based high-fat-diet mouse models leads to a reduction in adiposity and insulin resistance associated with T2D (24,25,56,(61)(62)(63), suggesting that cellular dysfunction is dependent on hydrocarbon chain length. These data support the rationale for our current evaluation of the impact of SFA hydrocarbon chain length on mitochondrial transport and function in the primary sensory DRG neurons damaged in DPN.…”
Section: Downloaded Frommentioning
confidence: 84%
“…Moreover, the Western diet, characterized by increased intake of foods with high levels of long-chain SFAs (LCSFAs), including myristate (C14:0), palmitate (C16:0), and stearate (C18:0), and low levels of beneficial medium-chain SFAs (MCSFAs), such as laurate (C12:0) (20-22), is a driving factor in the onset of dyslipidemia and T2D (23). MCSFAs are reported to prevent lipotoxicity and increase mitochondrial energy production (18,24,25). Likewise, equimolar caloric intake of MCSFAs and LCSFAs increases mitochondrial energy expenditure and leads to oxidative metabolic pathways as opposed to the metabolic dysfunction triggered by LCSFAs (24,26).…”
mentioning
confidence: 99%
“…Shorter fatty acid chains have lower melting points, can be easily metabolized, and have been associated with reduced autophagy, improved liver status, and lower insulin resistance. (18,19) This finding may be the result of changes in fatty acid synthesis, elongation, or oxidation with CHS-131 treatment. (20) In the liver, we observed an up-regulation of Fabp4 and Fasn with CHS-131 treatment, indicating increased fatty acid uptake and synthesis, and no changes in genes related to mitochondrial function and fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%